Comprehensive internationalisation at the URV Examples of good practices at the Universitat Rovira i Virgili - Gutiérrez-Colón Plana, Mar (Universitat Rovira i Virgili, 2017)
This book describes the practices implemented at the Universitat Rovira i Virgili to promote the university's internationalisation. This has been one of the URV's central objectives since it was created 25 years ago and will continue to be in the future. Internationalisation is one of the driving vectors behind all universities, the crucial element that allows them to be in constant dialogue with other institutions around the world, to stay at the cutting edge of knowledge, to recruit talent and to transmit knowledge.